A Collaborative Approach to Designing an Online Nutrition Education Program for People with Multiple Sclerosis - Russell, Rebecca Dawn (Curtin University, 2022)
This project has produced fundamental knowledge regarding the need and characteristics of a nutrition education program for people with multiple sclerosis (MS) and reinforces the importance of using co-design for end-user acceptability. The project has identified a theoretical framework and behaviour change techniques that support dietary behaviour change, as well as content, language, and design considerations for an online program that may improve the motivation of people with MS to make evidence-based, healthy dietary changes.